2006
DOI: 10.1093/humrep/del255
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B induces apoptosis and developmental injury in mouse embryonic stem cells and blastocysts

Abstract: Our results reveal for the first time that ginkgolide B retards the proliferation and development of mouse ESCs and blastocysts in vitro and causes developmental injury in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 56 publications
10
79
0
2
Order By: Relevance
“…Analysis of EB formation and MAP-2 expression in embryonic stem cells during NGF-induced cell differentiation confirmed that CTN caused early embryonic developmental injury (Figures 7A and 7B). Our previous studies demonstrated that apoptotic injury due to chemical treatment had significant negative effects on embryonic development [10,46]. In the present study, I have shown that CTN-induced apoptosis led to a high injury risk during early embryonic development.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Analysis of EB formation and MAP-2 expression in embryonic stem cells during NGF-induced cell differentiation confirmed that CTN caused early embryonic developmental injury (Figures 7A and 7B). Our previous studies demonstrated that apoptotic injury due to chemical treatment had significant negative effects on embryonic development [10,46]. In the present study, I have shown that CTN-induced apoptosis led to a high injury risk during early embryonic development.…”
Section: Discussionsupporting
confidence: 57%
“…EBs were generated as previously described [10]. Briefly, ESC-B5 cells were dissociated with trypsin-EDTA (0.25 %) and cultured in LIF (leukaemia inhibitory factor)-free stem cell medium to induce differentiation.…”
Section: Eb (Embryoid Body) Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that the reduction of oocyte maturation and blastocyst formation rates with this concentration of quercetin may result from unresponsive signaling to oocytes and embryos or direct embryo toxicity owing to excessive levels of flavonoids. Some groups have reported toxic effects of other flavonoids on embryos from different species [4][5][6]27]. In contrast, several investigations have shown that supplementation of porcine IVM medium with antioxidants such as selenium, vitamin E, and ascorbic acid decreases ROS levels while enhancing the developmental competence of IVF embryos and parthenotes [21,29,30].…”
Section: Discussionmentioning
confidence: 99%